Multinucleation resets human macrophages for specialized functions at the expense of their identity. (5th April 2023) - Ahmadzadeh, Kourosh; Pereira, Marie; Vanoppen, Margot; Bernaerts, Eline; Ko, Jeong‐Hun; Mitera, Tania; Maksoudian, Christy; Manshian, Bella B; Soenen, Stefaan; Rose, Carlos D; Matthys, Patrick; Wouters, Carine; et al.
Abstract :